EXPECTED RESULTS FROM THE IMPLEMENTATION OF ADMINISTRATIVE REFORMS - Mirzakhmedova Asemay (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
With the advent of mankind, he has been trying to take advantage of all the things and actions that he wants to carry out. What a person wants or wants to achieve, Of course, has been starting to carry out work on the plan after him, bringing his own plan to its implementation. It should be added that any conscious being lives in pursuit of a certain goal. In the universe as we know it, humans are the only conscious being, so long as we compare the state to man, because the society formed in the state is also made up of humans, which in conscious clarity come together and move forward towards a common goal. After independence, Uzbekistan also developed specific plans adapted to the market economy in all areas. But all these plans were developed based on the politics, economy and spirituality of that time, twenty-five years passed between them, the plans of that time were outdated, therefore, reforms in all areas, that is, new plans, began to be implemented. Including in the administrative sphere, reforms have become one of the most fundamental goals, since it was the sphere of the state mechanism with the factual circumstances that make our sphere the most limp and affect all spheres equally.